2010
DOI: 10.2527/jas.2008-1756
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gilt age at first estrus and breeding on third estrus on sow body weight changes and long-term reproductive performance1

Abstract: The objective of this trial was to determine the effect of age at first estrus on BW changes and long-term reproductive performance of sows. At approximately 100 d of age, prepubertal C22 gilts (n = 431) were allocated to trial. At a pen average of 140 d of age, gilts began daily direct contact with mature boars to stimulate onset of puberty. Gilts (n = 317, 73%) were recorded as cyclic by 180 d of age (select) and were classified on the basis of age at puberty into 3 puberty groups: 1) early puberty (EP; <153… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
103
0
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 24 publications
3
103
0
10
Order By: Relevance
“…Therefore, to obtain a high prolificacy in gilts, the size of the uterus in relation to their age, body weight, and growth rate should be carefully determined. Our previous study found that LY gilts in Thailand attained puberty at 196 days of age (Tummaruk et al 2007), which is about 2-4 weeks later than those in Europe and North America (Karlbom 1982;Patterson et al 2010). Mating decisions for gilts should therefore be made with caution because mating gilts at suboptimal time may result in inferior reproductive performance and longevity (Schukken et al 1994;Koketsu et al 1999;Tummaruk et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to obtain a high prolificacy in gilts, the size of the uterus in relation to their age, body weight, and growth rate should be carefully determined. Our previous study found that LY gilts in Thailand attained puberty at 196 days of age (Tummaruk et al 2007), which is about 2-4 weeks later than those in Europe and North America (Karlbom 1982;Patterson et al 2010). Mating decisions for gilts should therefore be made with caution because mating gilts at suboptimal time may result in inferior reproductive performance and longevity (Schukken et al 1994;Koketsu et al 1999;Tummaruk et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Age at first mating in gilts influences their subsequent reproductive performance as sows and their longevity (Koketsu et al 1999;Tummaruk et al 2001;Patterson et al 2010). Under field conditions, the reported age at first mating in gilts varies considerably from 150 up to 348 days (Tummaruk et al 2000), while the mean age at first mating in gilts varies among populations from 198 (Kummer et al 2006) to 268 days (Tummaruk et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that over the course of their whole lives sows rear an average of only 30-40 piglets (Patterson et al, 2010), thus the validity of a careful evaluation of the reproductive performance of sow determinants.…”
Section: Introductionmentioning
confidence: 99%
“…Dependendo das raças e tipos genéticos, as fêmeas suínas podem atingir a puberdade entre 5 a 9 meses de idade (MartiNat-botté et al, 2011). Reduzir esta variação, por meio do controle do início da puberdade, pode ser extremamente benéfico para a produtividade do rebanho, uma vez que as fêmeas que atingem a puberdade mais cedo tendem a permanecer mais tempo no rebanho e ser mais produtivas (PattersoN et al, 2010;. Por esse motivo, nas granjas mais tecnificadas tornou-se prática comum avançar a puberdade das marrãs utilizando terapia hormonal.…”
Section: Introductionunclassified